Nilai-Nilai Ajaran Islam Dalam Transaksi Jual Beli di Pasar Tradisional Kertapati Palembang - Nadila Dwi Safira; Anang Walian (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Values of Islamic Teachings in Buying and Selling Transactions at the Kertapati Palembang Traditional Market". This research is motivated by the lack of application of Islamic teaching values in buying and selling transactions at the Kertapati market in Palembang. The aim of this research is to determine the application of Islamic teachings in buying and selling transactions at the Kertapati Palembang traditional market and to determine the factors that influence buying and selling transactions at the Palembang Kertapati traditional market. The approach used in this research is a qualitative method with a descriptive approach. The data collection techniques include observation, interviews and documentation techniques using primary and secondary data. Meanwhile, the data analysis technique used is interactive analysis, namely data reduction, data presentation and drawing conclusions. The theory used in this research is Muhammad Lukman's theory relating to the values of Islamic teachings and Fadly Tjiptono's theory relating to the buying and selling process. Based on the results of this research, it is clear that the values of Islamic teachings have not been fully applied to buying and selling transactions at the Kertapati market, especially the occurrence of dishonesty both during the transaction process and the quality of the products being sold, and factors that influence the buying and selling process, namely those related to price fixing. inconsistent, as well as a lack of application of product quality and good service quality to buyers, but there are still many traders who have implemented the values of Islamic teachings, namely honesty, justice and halal products when making transactions at the Kertapati Palembang market. Thus, in order for the buying and selling transaction process at the Kertapati Palembang market to run well, it is best for sellers and buyers to be more consistent in applying the values of Islamic teachings so that a good relationship can be established between sellers and buyers.